STUDIES ON THE LARVICULTURE OF THE FRESHWATER FAIRY SHRIMP Streptocephalus torvicornis (ANOSTRACA: CRUSTACEA) - ASGARI S.M,; A. JAWAHAR ALI,; M.S. ARUN KUMAR, (International Journal of Pharma and Bio Sciences, 2014)
The present study is aimed to standardize the culture conditions of larviculture of Streptocephalus torvicornis. Effect of selected physico-chemical parameters such as temperature, salinity, hardness of different culture media on the survival of S. torvicornis larvae was studied. The effect of different feeds (baker’s yeast, rice bran and spirulina) on the survival was also tested. Furthermore, effect of nitrogenous metabolites (NO2-N, NO3-N) on the survival of S. torvicornis nauplius was recorded. The morphometric study revealed an overall specific growth rate of 2.3 mm/day. The baker’s yeast yielded a significantly highest survival rate (60 to 76%) after 48 hrs. Of the different temperatures tested, 20ºC was found to be optimum for the survival of S. torvivornis, whereas the 40º C was found to be lethal. The survival rate of nauplii in different salinities (0.15º/ºº, 0.3º/ºº and 2.5º/ºº) after 24 hrs ranged between 0 and 100%, whereas it was ranged between 0 and 63% after 48 hrs. Beyond 2.5º/ºº salinity, no survival of nauplii was noticed. A maximum survival rate of about 56% was noticed in the very hard medium, whereas it was only 16% in the very soft medium. Among the nitrogen metabolites, NO2-N was found to be more toxic. The results are discussed in the light of available literature.